White ascospore mutants in Ascobolus immersus: lack of the secondary spore wall, and allelism-testing - Veronica J. Marro; Bernard C. Lamb (Fungal Genetics Reports, 1995)
Ascospore pigmentation mutants have been very important in studies of gene conversion and crossing-over in such fungi as Neurospora, Sordaria and Ascobolus. Most such mutants are autonomous, with each haploid ascospore's genotype controlling its phenotype. In the Pasadena strains of Ascobolus immersus, where wild-type (+) ascospores are red/brown, we have autonomous white (w) mutants at several different loci. The white spores are completely unpigmented in + x w crosses, even though the apothecia and hyphae are a mixture of + and w genotypes. The developing w ascospores are surrounded by the same ascal sap as the + spores, yet do not develop pigment even if in contact with a + spore. Possible explanations for the non-pigmentation of white ascospores are: (i) they are structurally the same as red/brown + spores but cannot make the pigment even if some precursors are present in the ascus; (ii) the mutant ascospores could make the pigment but lack some suitable structure for it to form on - a parallel would be white-eyed Drosophila of w,w;Cn,Cn;Bn,Bn genotype, which have no eye pigment because they lack the pigment-attachment protein from W, although they can make pterins and ommochrome pigments from Cn,Bn. In case (ii), the lack of a structural feature in white ascospores might change other properties, such as optimum germination conditions.